Cold stress during winter over North India: Patterns, trends, and mortality risks - K. S. Athira; Raju Attada; Sulekha Komeravelli (PLoS ONE, 2026)
The cold temperatures during winter contribute to significant discomfort, causing cold stress to the lives of people. In this study, we investigate the cold stress conditions and their trends over north India during November – February for the period 1982−2020, using Universal Thermal Climate Index (UTCI), a widely recognized biometeorological variable. The onset of cold stress typically initiates in the late evening (18 IST) and gradually spreads across the north India. It then intensifies over night into moderate cold stress, persisting from 20 IST until the early morning hours (7 IST). Cold stress is found to be most intense in January, with UTCI values ranging between 0 °C to −13 °C among winter months. During cold wave events, cold stress reaches its maximum spatial extent and intensity throughout the study region, with the most intense conditions observed in Jammu & Kashmir and Ladakh. Results show a significant increase in slight cold stress hours during the winter season over the period 1982−2020 in north India. This increase reflects a transition from stronger cold stress categories to the slight cold stress category. Such a shift indicates a reduction in the severity of cold stress rather than an intensification of cold conditions. Slight cold stress occurs when UTCI values range between 0 °C and −9 °C and the duration of such conditions has increased at a rate of 33.64 hours per decade. This increase is most prominent in the high-altitude regions of Jammu & Kashmir, Ladakh and Himachal Pradesh. In contrast, moderate cold stress which occurs when the UTCI values are in the range −9 °C to −13 °C shows a significant decreasing trend, particularly in Rajasthan, Punjab, Haryana and Uttar Pradesh. Despite this, cold stress remains a major contributor to cold wave-related mortality in north India. Uttar Pradesh recorded the highest number of deaths of 4449, followed by Punjab (2606) and Bihar (2479). Although these states generally experience only slight cold stress with UTCI values in the range of 0 °C to 9 °C, the impact is amplified by wind chill with a category of ‘Tonic- very cold sub comfort’ caused by cold, dry northwesterly winds blowing directly into the region. This compound effect of cold stress and wind chill considerably enhances the mortality risk during cold wave events across north India.